Isolation and Identification of Lactic Acid Bacteria in Sudanese Fermented Camel Milk (Gariss) - Ahmed, Osman M. M.; El Owni, Osman A. O. (Journal of Veterinary Medicine and Animal Production, 2021)
This study was done in order to isolate, identify and determine the acidifying abilities of lactic acid bacteria present in traditional Sudanese fermented camel milk (Gariss). Eighteen samples of Gariss were collected during the period from September to November 2011 from nomadic camel herders in Butana region (Allahhween tribe), four of them from Al Gadarif state at Alshuack area (Gapat Alfeel), the rest (fourteen) were obtained from the nomads around Alsubag area. The study isolated 36 lactic acid bacteria which classified into five species. Acid production from different species in camel milk after 12 hours incubation were 0.52 % for Lactococcus lactis, 0.50% for Streptococcus thermophilus, 0.42% for Lactobacillus rhamnosus, 0.23% for Lactobacillus paracasei and 0.18% for Lactobacillus helveticus.